Where the rivers merge : a novel [large type] - Monroe, Mary Alice (William Morrow Large Print, 2025)
"1908: The Lowcountry of South Carolina is home to young Eliza Rivers, a free spirit who lives an idyllic life at her family's grand estate, Mayfield. She refuses to be confined by societal norms and spends her days exploring the vast property, observing wildlife, and riding horses. But the Great War, coastal storms, and family turmoil cut short her halcyon days, putting Eliza on a collision course with the patriarchal traditions of a bygone era. 1988: At eighty-eight, Eliza is the scion of the Rivers/Delancey family. She's fought a lifetime to save her beloved Mayfield and is too independent to quietly retire and leave the estate's fate to her greedy son. She must assure the future of the land and her family--or watch them both be split apart."--Cover p. [4].